Pemberdayaan Cabang Aisyiyah Ngampilan Yogyakarta melalui Literasi "Media Sehat" - Adhianty Nurjanah; Dyah Mutiarin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
We currently live amid the rapid development of communication systems and the media's tightness, which makes everyone aware of any information conveyed. The coverage of lies or hoaxes is the focus of attention, especially in online media. Hoax is information that is engineered to cover up real information. Based on the Community Service Team's interviews and observations with partners, PCA members and administrators are acting as consumers of mass media, especially TV and internet media, namely WA, as daily information media. In its management activities, media literacy has never been carried out, even though media literacy needs an empowered and information literate society. Thus, Community Service will be carried out through this community service activity in the form of Empowerment of Aisyiyah Ngampilan Branches through Healthy Media Literacy. The method carried out by the community service team is workshops related to the importance of media literacy in dealing with hoaxes; media literacy assistance in dealing with hoaxes; digital-based "Tabayun on information to be smart as a media literate person"; making a guide book for Healthy Media Literacy; Smart As Media literate individuals face hoaxes"; providing facilities for the Aisyiyah Ngampilan Branch office that can be used to support management activities of the Aisyiyah Ngampilan Yogyakarta Branch. This Muhammadiyah-based community service is the increased ability of the board and members, especially related to healthy media literacy in dealing with hoaxes.